2021
DOI: 10.1021/acssuschemeng.0c09068
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Superhydrophobic Absorption-Dominated Electromagnetic Shielding Material by Building Clustered Fe3O4 Nanoparticles on the Copper-Coated Cellulose Paper

Abstract: Corrosion-resistant electromagnetic shielding materials with high conductivity and excellent magnetic properties are urgently needed to resolve the issue of electromagnetic radiation pollution. Herein, the renewable and easily degradable cellulose paper after tannin-assisted silver-nanoparticle deposition was designed as the substrate. An electroless copper-plated paper (ECP) with a high conductivity of 4167 s/cm and a low sheet resistance of 5.17 mΩ/sq was used as a conductive layer. The superhydrophobic magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 40 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…As shown in Figure d, the peak fitting of the C 1s XPS spectrum of MWCNTs-COOH in MF can be divided into three components with different binding energies; the binding energy peaks at 284.8, 286.4, and 288.8 eV originated from CC, C–O, and carboxyl CO, respectively. The peaks of Fe 2p (Figure e) located at 711.2 and 724.3 eV correspond to the Fe 2p 3/2 and Fe 2p 1/2 core-level spectra of Fe 3 O 4 , respectively, and there are no binding energy peaks for γ-Fe 2 O 3 , precluding the appearance of γ-Fe 2 O 3 in the MF . In addition, the O 1s XPS spectrum of MF (Figure f) can be divided into three oxygen components with different binding energies: O 1s of Fe 3 O 4 (529.8 eV), OH (531.6 eV), and H 2 O molecules (533.0 eV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure d, the peak fitting of the C 1s XPS spectrum of MWCNTs-COOH in MF can be divided into three components with different binding energies; the binding energy peaks at 284.8, 286.4, and 288.8 eV originated from CC, C–O, and carboxyl CO, respectively. The peaks of Fe 2p (Figure e) located at 711.2 and 724.3 eV correspond to the Fe 2p 3/2 and Fe 2p 1/2 core-level spectra of Fe 3 O 4 , respectively, and there are no binding energy peaks for γ-Fe 2 O 3 , precluding the appearance of γ-Fe 2 O 3 in the MF . In addition, the O 1s XPS spectrum of MF (Figure f) can be divided into three oxygen components with different binding energies: O 1s of Fe 3 O 4 (529.8 eV), OH (531.6 eV), and H 2 O molecules (533.0 eV).…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that the introduction of magnetic nanoparticles can provide hysteresis loss to promote EMI SE and further reduce the reflection coefficient through reaching the appropriate impedance matching between a free space and material surface. , Until now, some magnetic carbon nanofillers have been used to attenuate EM waves through dielectric loss and hysteresis loss, thereby reducing secondary pollution. However, it is hard for magnetic nanoparticles to attain high EMI shielding performance due to its low electrical conductivity . A sandwich-structured EMI shielding film, in which Fe 3 O 4 @AEWC (FA)/cellulose nanofiber serves as an absorbing layer and highly conductive MXene as a reflecting layer, was designed, and the EMI SE reached 63.8 dB with a reflection coefficient value of 0.67 .…”
Section: Introductionmentioning
confidence: 99%
“…In some situations dominated by EMI absorption, 144 shielding materials with satisfactory EMI absorption have received attention. Zhang et al 145 reported a superhydrophobic absorption-dominated electromagnetic shielding material by introducing clustered Fe 3 O 4 nanoparticles on copper-coated cellulose paper. The clustered Fe 3 O 4 microspheres with excellent magnetic and conductive properties can facilitate EMW effective dissipation, and multiple reflections and scattering, causing more EMW absorption between the copper-plated and magnetic layers.…”
Section: Cellulose-based Papermentioning
confidence: 99%
“…Recently, the introduction of magnetic nanoparticles have been considered an effective way to reduce the re ection loss because of their high saturation magnetization strength [25]. Mostly used carbon nano llers provide dielectric loss to the shielding materials and then the total shielding effectiveness is mainly from the re ection of EM waves [26,27].…”
Section: Introductionmentioning
confidence: 99%